The Prediction of Broad Puddle Change Based on Land Subsidence Analysis in Semarang - Pratikso Pratikso; Rahmat Mudiyono; Bagas Wahyu Adhi (International Conference on Coastal and Delta Areas, 2017)
Semarang is the capital city of Central Java that has a population about 1.3 million people, the position of Semarang is very strategic as a regional transport. Semarang is divided into 2 parts namely Semarang Upper area and Semarang lower area. The soil layer of Semarang lower area is dominated by soft alluvial soil layers that continue to occur compression. These conditions effect this area most likely get the environmental impact caused by land subsidence. The objective of this study was to determine the large and duration of land subsidence that occurred in Semarang Barat district and its influence towards the area of inundation. The analysis of this research used 1D terzaghi method and plaxis software which then in overlay using GIS which yielded map of subsidence in the area. The calculation results that used 1D Terzaghi, the land subsidence of Mediterranean Housing was 91.11 cm for 27.11 years, Ronggolawe area subsidence was 24.40 cm for 18,50 years, and Jendral Sudirman area was 10 cm for 15,94 years, while using plaxis 8.2 software, the Perum Mediterania was 93.40 cm, Ronggolawe area was 26.22 cm, Jendral Sudriman area was 13.68 cm. Changes in the area of inundation in 2017 to 2047 amounted to ± 924,74 ha. Keywords: Land Subsidence, 1D Terzaghi, GIS, Plaxis